Analysis of short interfering RNA function in RNA interference by using Drosophila embryo extracts and schneider cells. - Lipardi, C.; Baek, H.J.; Wei, Q.; Paterson, B.M. (Methods in Enzymology, 2005)
The realization that short double-stranded RNA (dsRNAs) 21-25 bp in length represent the basis for posttranscriptional gene silencing (PTGS) in plants, quelling in N. crassa, and RNA interference (RNAi) in C. elegans and Drosophila has given insight into one of the most evolutionarily conserved pathways in eukaryotes. dsRNA that arises due to viral infection, transposon mobilization, random insertion of transgenes near active promoters, transcripts from repetitive elements in the genome, or introduction of exogenous dsRNA directly is processed by one of the RNase III-related enzymes, known as the Dicers, to produce 21- to 25-bp short dsRNAs or short interfering RNAs (siRNAs) that target the degradation of the cognate RNA sequence (Denli and Hannon, 2003; Hannon, 2002; Plasterk, 2002). Proteins in the RNAi pathway and siRNA-like RNAs have also been recently demonstrated to play a role in the formation and maintenance of heterochromatin in S. pombe as well as in transgene-induced PTGS in Drosophila (Hall et al., 2002; Pal-Bhadra et al., 2004; Volpe et al., 2002). An understanding of siRNA function in these crucial regulatory pathways requires biochemical approaches to study siRNAs and their role in gene silencing as well as the formation and maintenance of heterochromatin. This chapter describes simple methods for using Drosophila embryo extracts and cultured insect cells to study siRNA function in the RNAi pathway in vivo and in vitro. We describe the most recent protocols for the preparation and use of Drosophila embryo extracts used in gene targeting studies. We present methods we have used to assay siRNA function in Drosophila embryo extracts and in cultured SL2 cells that demonstrate a combined role for siRNAs and RNA-dependent RNA polymerase (RdRp) activity in Drosophila RNAi.